Spin Doctoring. - Hellemans, A. (IEEE spectrum)
Researchers at the University of California, Los Angeles, introduce a concept for replacing copper connections on chips. The concept relies on atomic spin, a quantum-mechanical property related to magnetism, and on waves generated when that spin is disturbed. Atomic spin arises from the magnetic fields generated by an atom's spinning electrons. Both atomic and electron spin can be thought of metaphorically as rotation, but they are in fact abstract properties and are represented as vectors that can point either up or down - that is, either parallel or perpendicular to magnetic field lines. Eshaghian-Wilner and her colleagues have presented possible designs for VLSI architectures that would use spin waves to transmit data between processors. The simplest one consists of a number of pairs of conductor bars in a circle on a ferromagnetic film. Each pair of strips can either transmit or receive data, and several data streams; can be transmitted simultaneously by creating spin waves of different frequencies